Potential of Microencapsulation of Trash Fish-Based Feed Enriched with Sauropus androgynus Leaf Extract to Increase Ovary Maturity Rate of Mangrove Crab (Scylla serrata) - Lembang, Miska Sanda; Fitri, Syahrani; Oktapriani, Intan Ayu; Purnamasari, Nursyabhila Auliana; Erik, Erik (Department of Aquaculture, 2025)
Mangrove crabs (Scylla serrata) are one of the leading fishery commodities in North Kalimantan and have high export value. One of the factors in the development of ovarian maturity in mud crabs is through feed. This research aimed to assess the nutritional levels and maturity of the ovaries of mud crab mothers using encapsulated feed enriched with S. androgynus leaf. The research design used was a Completely Randomized Design (CRD) with three treatments and three replications. Mangrove crabs are reared for 20 days, feeding 5% of body biomass. The treatments in this study were Control (Trash Fish Feed), A (Trash fish meal + S. androgynus leaf extract), and B (Encapsulation). Microscopic observations showed that the encapsulated feed was successful in forming microencapsulated granules. Measuring the nutritional content of feed, including protein, fat, carbohydrates, and ash from test samples, it was found that treatment B of encapsulated feed provided optimal nutritional content values ​​compared to other treatments. Observation of ovarian maturity morphology showed TKG IV at 20 days of testing with encapsulated feed. The gonad maturity index (GMI) value of the encapsulated feed gave the highest value and significantly differed from the control and non-encapsulated treatments. This is by the hepatopancreatic index (HSI) value, which is inversely proportional to the GMI value due to being synthesized into oocytes in the mangrove crab ovaries, thus reducing the HSI value. Therefore, it can be concluded that based on the results of research on morphological observations, gonad maturity index, and hepatopancreas index, feed enriched with encapsulated S. androgynus leaf extract shows more significant performance in increasing the rate of gonad maturity of mud crabs.